RELEASE OF ALL LEGAL DEMANDS (ONTSLAG VAN RECHT VERVOLGING) IN JUDGMENT'S CONSIDERATION - Andi Kusuma Mapareppa; Jawade Hafidz (Universitas Islam Sultan Agung, 2020)
This study aims to identify and explain the basic position of judges' considerations in issuing a decision free from all lawsuits for the accused and to analyze the development of law, law science and legal information technology and to adjust legal theory and legal practice for the sake of a sense of justice in society. This study uses a normative juridical approach. which refers to the applicable laws and regulations by examining secondary data on the principle of legal certainty, the principle of legal justice, the principle of legal usefulness as regulated in law number 4 of 2009 concerning Judicial Power. Based on the results of this study, there are differences in the meaning or terms between a release decision and an acquittal decision. In the judge's consideration in the case decision No.627 / Pid / Sus / 2018 / PN.Smg, in his consideration the judge stated that the defendant's actions were proven but not a criminal act as in the indictment of the public prosecutor and in accordance with the Semarang District Court judge in imposing a crime having considered juridical, sociological and philosophical considerations, in deciding the decision to be released from all lawsuits (ONTSLAG van RECHTVERVOLGING) based on article 191 paragraph (2) of the Criminal Procedure Code, which reads